PENINGKATAN PENYUSUNAN LAPORAN KEUANGAN BAGI MAHASISWA SEBAGAI MODAL LULUSAN BERMUTU DENGAN MENGGUNAKAN APLIKASI MYOB - Totok Susilo Pamuji Nugroho (JAMER : Jurnal Akuntansi Merdeka, 2025)
This study aims to analyze the improvement of students’ ability in preparing financial statements through the implementation of the MYOB application. The research employed research method involving 24 students of the Accounting Study Program, STIE Atma Bhakti, Class A, from the 5th and 6th semesters. Data were collected through financial statement practice tests, observations, and interviews, and validated using triangulation techniques.The results show that students’ ability to prepare financial statements manually was still limited, with only 37.5% of students able to correctly produce simple financial reports. After applying MYOB in the learning process, there was a significant improvement, with 60% of students successfully preparing financial statements according to the minimum mastery criteria. This improvement was supported by real business transaction simulations, the lecturer’s role as a facilitator, and the user-friendly features of MYOB.The conclusion of this study is that MYOB is effective in enhancing students’ skills in preparing financial statements, although some students still require assistance, particularly in handling more complex transactions. The limitations of this research include the small number of subjects, the relatively short research duration, and the focus that was more oriented toward technical skills.